Determinan Variabel Makroekonomi Terhadap Kemiskinan di Indonesia - Nurul Hidayati; Ariusni Ariusni (Universitas Negeri Padang, 2019)
This study aims to determine and analyze the effects of (1) Economic Growth, (2) Unemployment and (3) Poverty Alleviation Poverty Policy in Indonesia using the method of multiple linear equations (OLS). The results of estimation of multiple linear equations show that (1) economic growth with national income indicators has a significant negative effect on poverty in Indonesia, (2) unemployment has a significant positive effect on poverty in Indonesia, (3) poverty alleviation policies have no significant negative effect on poverty in Indonesia. Indonesia. Based on the results of this study, the government is expected to be able to make certain policies and programs for the poor through increasing economic growth, development and providing employment for unemployed people and it is hoped that poverty reduction policies made by the government can reduce poverty in Indonesia.